Evaluation of alkali reactivity of concrete aggregates via AC impedance spectroscopy. (1st August 2017) - Shi, Tao; Zheng, Liwei; Xu, Xiuchao
Highlights: The alkali reactivity of concrete aggregates was evaluated by AC impedance spectroscopy. Results of AC impedance spectroscopy are compared with linear expansion ratio and relative dynamic elastic modulus. AC impedance spectroscopy can be used to test and evaluate the alkaline reactivity of concrete aggregates. Abstract: The alkali reactivity of concrete aggregates was evaluated by AC impedance spectroscopy as the main method along with linear expansion ratio, relative dynamic elastic modulus, and mercury intrusion porosimetry tests. The electrochemical parameters of AC impedance spectra showed a close relationship with the hydration reaction and microstructure of cement-based materials. The results obtained by the linear expansion ratio, the relative dynamic elastic modulus, and the pore structure characteristics were basically consistent with those obtained by the impedance spectra. Therefore, the ASR trend shown by the resistance in AC impedance spectra, Rs, and the phase angle θ, can be considered as basically reliable. The intensity of the ASR of concrete changed with different contents of alkali aggregates. The test showed that in the ASR at an early age, the ratio between the active and inactive aggregates had the worst point. As the content of active alkali aggregates was at the worst point, the ASR led to the maximum expansion ratio and caused the most severe harm to the concrete specimens.